2022
DOI: 10.3390/systems10040116
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Decision-Making System for Advertising Strategies of Small Enterprises—Focusing on Company A

Abstract: In the post-COVID-19 era, the founding rates of micro enterprises and startups will increase due to the low youth employment rates and increased retirement of baby boomers. Therefore, the portion of small enterprises among all enterprises is expected to grow. The rapid change in consumption patterns due to the COVID-19 pandemic has accelerated the entry of small enterprises into the online advertising market. However, advertising costs spent in running the businesses are taking up a large portion of their sale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This means that the average asset size influences the perceived effectiveness of Facebook utilization in terms of sales volume. These findings were supported by the study of Jeong et al (2022), which indicated that online advertising has a different range of advertising expenditure depending on the microenterprise's advertising platform. Based on their findings, most micro and small enterprises were forced to invest almost 50% or more of their sales in advertising costs due to their limited budget.…”
Section: Significant Differences Between Business Profiles and Percei...mentioning
confidence: 60%
See 1 more Smart Citation
“…This means that the average asset size influences the perceived effectiveness of Facebook utilization in terms of sales volume. These findings were supported by the study of Jeong et al (2022), which indicated that online advertising has a different range of advertising expenditure depending on the microenterprise's advertising platform. Based on their findings, most micro and small enterprises were forced to invest almost 50% or more of their sales in advertising costs due to their limited budget.…”
Section: Significant Differences Between Business Profiles and Percei...mentioning
confidence: 60%
“…Facebook pages and groups have become crucial for businesses to advertise on media networks. Moreover, a study by Jeong et al (2022) indicated that the pandemic has increased micro and small businesses engaged in various business strategies. The study used optimization analysis with simulation modeling and found that online advertising continuously develops and can track clicks and viewers.…”
Section: Facebook Use In Advertisingmentioning
confidence: 99%
“…After all, the rapid communication of digital communication also requires highly skilled communicators or artists who could require high fee standards. In the post-COVID-19 era, the entry of small enterprises has accelerated into the online advertising market, and various advertising platforms cost spent or budget (Jeong et al, 2022). Overall, this research takes the engagement aspect as the main concern of constructing the digital advertisement because it is assumed that successfulness of engagement is an obligation and entry point for other aspects' success of a digital advertisement to be accepted by viewers.…”
Section: Introductionmentioning
confidence: 99%